2014
DOI: 10.1007/s00449-014-1215-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical and chemical properties of HTSXT-FTIR samples on the quality of prediction models developed to determine absolute concentrations of total proteins, carbohydrates and triglycerides: a preliminary study on the determination of their absolute concentrations in fresh microalgal biomass

Abstract: Absolute concentrations of total macromolecules (triglycerides, proteins and carbohydrates) in microorganisms can be rapidly measured by FTIR spectroscopy, but caution is needed to avoid non-specific experimental bias. Here, we assess the limits within which this approach can be used on model solutions of macromolecules of interest. We used the Bruker HTSXT-FTIR system. Our results show that the solid deposits obtained after the sampling procedure present physical and chemical properties that influence the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, it should be noted that our study has covered one order of magnitude higher range of glucose concentration (up to 80 g L −1 glucose) compared to the one in the above mentioned study [ 27 ]. The only previous reported HTS measurement of glucose, where similarly high concentrations of glucose were measured in an artificial set of model solutions (and not an actual cultivation medium), has resulted with very large errors of prediction [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that our study has covered one order of magnitude higher range of glucose concentration (up to 80 g L −1 glucose) compared to the one in the above mentioned study [ 27 ]. The only previous reported HTS measurement of glucose, where similarly high concentrations of glucose were measured in an artificial set of model solutions (and not an actual cultivation medium), has resulted with very large errors of prediction [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis is usually achieved by depositing biomass samples on a multi-well IR-light-transparent microplate [ 7 10 , 24 26 ]. Several studies have shown a high correlation of HTS FTIR spectroscopy with traditional analytical techniques, such as GC, HPLC, and biochemical assays, for different types of bioprocesses [ 7 , 9 , 27 , 28 ]. However, the majority of studies have been focused on quantitative analysis of biomass, while high-throughput studies of substrates and extracellular metabolites had very limited scope [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbance spectra were collected between 4 000 cm -1 and 700 cm -1 with 30 scans and averaged. The spectra were analyzed by the integral ratios method [50]. The lipid signature was associated with the ester bond (Eb) signal (~1740 cm -1 ), whereas the carbohydrate signature was associated with the C-O-C signal of the polysaccharides (~1200–900 cm -1 ) [37] and the protein signature associated with the amide II band (~1540 cm -1 ) of the N-H of the amides associated with the proteins.…”
Section: Methodsmentioning
confidence: 99%
“…For that purpose, numerous approaches have illustrated the effect of the microalgae culture conditions on the molecular determinants that trigger lipids production [11][12][13] and the physiological modifications associated. [14][15][16][17] However, it is still difficult to understand the relationship between the metabolic fate of the carbon, the fine chemical characterization of the accumulated lipids, and the physiological adaptation of the microalgae during the biosynthesis accumulating lipids in the form of droplets.…”
Section: Introductionmentioning
confidence: 99%